Framework Model for Sustainability Reliability Assessment of Clinical Laboratory Equipment in Indonesian Vertical Hospitals: Contributing to SDG 3 - Fitria Hanaris; Yatim Riyanto; Nunuk Hariyati (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2026)
Objective: This study aims to develop a holistic framework for assessing the reliability of clinical laboratory equipment in vertical hospitals in Indonesia. Clinical laboratories play a strategic role in supporting National Health Insurance and in achieving the Sustainable Development Goals (SDGs) across economic, social, and environmental dimensions. Reliable maintenance systems are crucial for ensuring equipment reliability, maintainability, availability, and safety. Method: A comprehensive literature review of international journals was conducted to identify existing models and methodologies for reliability assessment. The proposed framework integrates reliability engineering, sustainability principles, and VUCA (volatility, uncertainty, complexity, ambiguity) concepts. The model consists of sub-assessment sections covering pre-analytical, analytical, and post-analytical stages, as well as equipment reliability, logistics and warehousing, and continuous equipment monitoring. Results: The framework provides a structured approach for identifying factors that influence the reliability of laboratory equipment, enabling effective assessment and problem-solving in clinical laboratories. It facilitates continuous evaluation, supports maintenance planning, and aligns with safety and quality standards. Novelty: Integrating reliability, sustainability, and VUCA concepts into a single, holistic framework for clinical laboratory equipment in Indonesian vertical hospitals. The proposed framework provides practical guidance for hospital policymakers and managers to ensure accurate testing results, optimize equipment performance, enhance patient safety, and support sustainable healthcare operations. By strengthening the reliability of diagnostic services and improving the quality and accessibility of healthcare delivery, this framework contributes to achieving SDG 3 (Good Health and Well-Being).